Peran Business Intelligence dalam Mendukung Pengambilan Keputusan pada Usaha Kecil Berbasis Data Transaksi: The Role of Business Intelligence in Supporting Decision Making in Small Businesses Based on Transaction Data - Selvia Ayu Putri Ananda; Muhammad Irwan Padli Nasution (Pendidikan Al-Gafari, 2026)
The advancement of the digital era has encouraged small businesses to be more adaptive in managing their business information. One fundamental issue frequently encountered is the inability to process transaction data stored in database systems into useful information for business decisions. This research employed a literature review method, analyzing several scientific articles published between 2022 and 2025 from various indexed national journals. The analysis revealed that BI implementation significantly contributes to supporting small business decision-making, including its ability to identify sales trends, provide automated reports, and support strategic planning based on transaction data. Despite the benefits offered, small businesses still face a number of obstacles in adopting this technology, such as limited human resource competency and technological infrastructure constraints.